2020
DOI: 10.1021/acsami.0c11154
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Layer MoS2xTe2(1–x) Ternary Alloys: Two-Dimensional van der Waals Growth, Band gap Engineering, and Electrical Transport

Abstract: Ternary alloys in two-dimensional (2D) transition-metal dichalcogenides allow band gap tuning and phase engineering and change the electrical transport type. A process of 2D van der Waals epitaxial growth of molybdenum sulfide telluride alloys (MoS2x Te2(1–x), 0 ≤ x ≤ 1) is presented for synthesizing few-atomic-layer films on SiO2 substrates using metal–organic chemical vapor deposition. Raman spectra, X-ray photoelectron spectra, photoluminescence (PL), and electrical transport properties of few-atomic-layer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…In this regard, flat substrate materials (such as silicone, metal blocks, glass, etc. ) or cubic ,, and sheet-like nano-/microscale templates (such as salt crystals, graphene, etc. ) ,, are highly useful.…”
Section: Ssrs For the Synthesis Of Nanomaterialsmentioning
confidence: 99%
“…In this regard, flat substrate materials (such as silicone, metal blocks, glass, etc. ) or cubic ,, and sheet-like nano-/microscale templates (such as salt crystals, graphene, etc. ) ,, are highly useful.…”
Section: Ssrs For the Synthesis Of Nanomaterialsmentioning
confidence: 99%
“…Inset shows the atomic structure of the alloy. (C) The shifting of VB of MoS 2x Te 2(1−x) as a function of S ( Kim et al., 2020 ) (D) Device structure of OLED. (E) Current density and luminance–voltage curve of the fabricated OLEDs ( Kwon et al., 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“… (C) The shifting of VB of MoS 2x Te 2(1−x) as a function of S ( Kim et al., 2020 ) (D) Device structure of OLED. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it has been used to grow tunable MoS 2(1-x) Te 2x alloy films wherein Se and Te are both from MO precursors. [146] New efforts for diversifying doped and alloyed samples grown by MOCVD should be spent on exploring metal or magnetic dopants and their corresponding MO precursors with a high or intermediate vapor pressure. It has been found that even with only CH-free molecules such as W(CO) 6 and H 2 Se involved in MOCVD of WSe 2 , the carbon impurities with a concentration of 225 ppm were still detected via STM/STS.…”
Section: Discussionmentioning
confidence: 99%